Editorial Information for The Advocate: Spring/Summer 2019 Issue (The Advocate, 2019)
This Spring/Summer 2019 Editorial Information page provides a farewell statement from Dr. Bruce Quantic who has served as the editor of The Advocate for many years. Members of The Advocate's Editorial Review Board, information regarding the nature of The Advocate and how you can become a member of the Association of Teacher Educators- Kansas is found here.